1990
DOI: 10.1088/0268-1242/5/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Surface phonons in GaAs cylinders

Abstract: Raman scattering from arrays of GaAs quantum cylinders with radii down to 30 nm has been observed. The spectra show an enhanced TO phonon intensity due to a change in the first-order selection rules. In addition, the smallest cylinders exhibit an extra spectral feature between the TO and LO phonons. The behaviour of this additional peak as a function of the scattering geometry, the cylinder size and the variation of the medium surrounding the cylinders is consistent with a theoretical model of the surface phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 21 publications
6
58
0
Order By: Relevance
“…They are solutions to Maxwell's equations with appropriate boundary conditions [B. E. Sernelius, 2001]. Many authors have studied theoretically the SO-modes from different geometries (cylindr ical and spheroids shape) in nanoparticles, nanowires and QDs, by using the approximation of a dielectric continuum and modeling of valence-force fields to explain the connection between SO phonon modes and the geometrical shape of a semiconductor QD [] [Watt M et al, 1990;-37, Gupta R et al, 2203 -38]. In our samples we observed that the integrated Raman intensity, and the position of the SOmode for the samples M3 -M4 is clearly dependent of the volume and facets formed on SADQs.…”
Section: Fig 7 Raman Spectra Taken At Room Temperature Of the Inas mentioning
confidence: 99%
“…They are solutions to Maxwell's equations with appropriate boundary conditions [B. E. Sernelius, 2001]. Many authors have studied theoretically the SO-modes from different geometries (cylindr ical and spheroids shape) in nanoparticles, nanowires and QDs, by using the approximation of a dielectric continuum and modeling of valence-force fields to explain the connection between SO phonon modes and the geometrical shape of a semiconductor QD [] [Watt M et al, 1990;-37, Gupta R et al, 2203 -38]. In our samples we observed that the integrated Raman intensity, and the position of the SOmode for the samples M3 -M4 is clearly dependent of the volume and facets formed on SADQs.…”
Section: Fig 7 Raman Spectra Taken At Room Temperature Of the Inas mentioning
confidence: 99%
“…This model was successfully applied to describe the SO phonon spectra of microcrystalline spheres [44], GaAs NWs [47], Si NWs [48], and GaAs cylinders [50].…”
Section: Surface Optical (So) Phononsmentioning
confidence: 99%
“…In the past, several workers [10][11][12][13][14][15] had carried out studies of the electron interaction with longitudinal optical (LO) phonons in quantum wires considering the modification of the electron energy spectrum and wave function due to their space localization but assuming the bulk forms for LO phonon modes. However, it was shown that the reduced sized scale and dimensionality have great influence leading to phonon confinement and changes in phonon modes [16][17][18][19]. These changes become an essential part of the description of electron-phonon interaction and affect strongly the transport properties of electrons in quantum wires.…”
Section: Introductionmentioning
confidence: 99%